Comparison of BTB Superfamilies in Physcomitrella patens and Arabidopsis thaliana. - Janssen, Jacob (My University, 2009)
Following their synthesis, proteins in cells can be modified in a variety of ways. These modifications may modulate the protein's activity, localization, interactions with other molecules, or stability. One such modification is the covalent attachment of a small globular protein called ubiquitin (Ub). Dr. Gingerich has previously characterized the BTB family in a dicotyledenous flowering plant, Arabidopsis thaliana. In this studied, I have begun to characterize the family in a simple nonvascular moss, Physcomitrella patens.
Color poster with text and diagrams.
Keywords: Ubiquitin; Physcomitrella patens--Genetics; Arabidopsis thaliana--Genetics; Proteins--Research; Posters